2021
DOI: 10.1039/d0qi01446j
|View full text |Cite
|
Sign up to set email alerts
|

(γ-Methoxy propyl amine)2PbBr4: a novel two-dimensional halide hybrid perovskite with efficient bluish white-light emission

Abstract: White-light emission in Lead halide hybrid perovskites has attracted increasing attention due to their significant applications in the field of light-emitting devices. Despite tremendous efforts, the two-dimensional (2D) white-light emissive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…It is found that 1 shows an absorption edge at ∼400 nm (Figure 6), which directly indicates compound 1 is an indirect band gap semiconductor. The absorption edge is comparable with another hybrid perovskite of C 12 H 28 Br 4 N 4 Pb, [23] (γ‐methoxy propyl amine) 2 PbBr 4 [24] …”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…It is found that 1 shows an absorption edge at ∼400 nm (Figure 6), which directly indicates compound 1 is an indirect band gap semiconductor. The absorption edge is comparable with another hybrid perovskite of C 12 H 28 Br 4 N 4 Pb, [23] (γ‐methoxy propyl amine) 2 PbBr 4 [24] …”
Section: Resultsmentioning
confidence: 56%
“…The absorption edge is comparable with another hybrid perovskite of C 12 H 28 Br 4 N 4 Pb, [23] (γ-methoxy propyl amine) 2 PbBr 4 . [24] According Tauc equation, the band gap of 1 was estimated to 2.78 eV (intercept value of a plot of (F(R 1 )hv) 1/2 -Energy; inset at Figure 7). The band gap is smaller than that of the based on acyclic cations phase transition material (C 6 H 14 N) 2 PbBr 4 (3.05 eV), [25] which could be used in high power/ efficiency optoelectronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…[99][100] The corrugated (110)-family of lead halide perovskites has been extensively pursued due to the associated, characteristic broadband emission where the majority of the materials are (110)-lead bromide perovskites (Table 2). [92,100,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] There has been great pursuance in defining structural prerequisites for the targeted and rational design of (110)-orientated perovskites. Initially, (API)PbBr 4 can be tracked as the first (110)lead bromide perovskite reporting broadband emission, in which API = 1-(3-Aminopropyl)imidazole.…”
Section: Thin-layer Lead Bromide Perovskites (N = 1) With (110) Orien...mentioning
confidence: 99%
“…[92,119,[126][127][128][129]134] For comparative purpose among the (100)-orientated perovskites, (C 6 H 16 N 2 ) PbBr 4 [129] (C 6 H 16 N 2 : 2-methyl-1,5-diaminopentylammonium) features the highest CRI value of 91. (TMPDA)PbBr 4 [140] (TMPDA = N,N,N,N-tetramethyl-1,4 phenylenediammonium) features the highest PLQY of 12.8 %, followed by (C 4 H 13 NO) 2 PbBr 4 [120] (C 4 H 13 NO = γ-Methoxypropylammonium) with PLQY of 6.85 % (Table 2).…”
Section: Thin-layer Lead Bromide Perovskites (N = 1) With (110) Orien...mentioning
confidence: 99%
“…These characterizations endow the bulk low‐dimensional perovskites with ultrahigh luminescent efficiency, which is independent of material morphologies and particle sizes. Especially, the 2D layered perovskites possess natural quantum well characterizations, in which the well and barrier width mainly dependent on the thickness of inorganic layer [39–41] . Therefore, it is convenient to fine‐tune the confinement and exciton binding energy through rationally controlling the thickness of inorganic layer.…”
Section: Introductionmentioning
confidence: 99%